A scalable routing protocol for hybrid wireless mesh networks - Mahmod, Zainab Senan; Hassan Abdalla Hashim, Aisha (2012)
Wireless mesh networks (WMNs) have emerged as a key technology for next-generation wireless networking. However, several challenging research issues need to be resolved. One of the most effective factors to be improved is the routing protocol used to be robust, scalable, secured and efficient. This paper aims to design and implement a routing protocol that improves the scalability of the WMNs. The Directional Hierarchical AODV (DH-AODV) routing protocol is proposed taking advantage of the existing fields in the AODV's control packets in order to reduce the load on the network's bandwidth and to quickly detect route breakage. The proposed protocol is designed, implemented and evaluated using Qualnet Simulator. The simulation results indicate an improvement of DH-AODV over the standard AODV.